(untitled) (Conferencea, 2022)
The work of a continuous two-span beam with combined reinforcement of steel and composite reinforcement under the action of concentrated forces is considered. On the basis of computer simulation using a three-dimensional model, the nature of the stress-strain state of the structure was investigated. In total, five models of beams with different characteristics were considered. Based on the results of a numerical study, data were obtained on the distribution of stresses and displacements in continuous beams.